Penguatan Kapasitas Kewirausahaan Mahasiswa TGBC Thailand melalui Pelatihan Business Model Canvas Berbasis Kreativitas dan Keberlanjutan - Putra, Syaifurrizal Wijaya; Akbar, Rasyidi Faiz; Andjarwati, Anik Lestari; Ramadhan, Dyandra Armyta (Abimanyu : Jornal of Community Engagement, 2026)
Students at the Thai Global Business Administration Technological College (TGBC) face limitations in identifying and developing business ideas relevant to market needs. This Community Service Program (PKM) aimed to equip students with practical skills in designing a creative and sustainable Business Model Canvas (BMC). The method used was interactive training, including lectures, discussions, simulations, and practical exercises. Evaluation was conducted using pre-test and post-test instruments. Results show that more than 85% of participants improved their understanding of creative and sustainable business management and felt more confident and motivated to apply BMC. Therefore, this PKM program effectively enhanced TGBC students’ entrepreneurial capacity while supporting the development of a sustainability-oriented business ecosystem. hai Global Business Administration Technological College (TGBC) face limitations in identifying and developing business ideas relevant to market needs. This Community Service Program (PKM) aimed to equip students with practical skills in designing a creative and sustainable Business Model Canvas (BMC). The method used was interactive training, including lectures, discussions, simulations, and practical exercises. Evaluation was conducted using pre-test and post-test instruments. Results show that more than 85% of participants improved their understanding of creative and sustainable business management and felt more confident and motivated to apply BMC. Therefore, this PKM program effectively enhanced TGBC students’ entrepreneurial capacity while supporting the development of a sustainability-oriented business ecosystem.